Lower diurnal HPA-axis activity in male hypertensive and coronary heart disease patients predicts future CHD risk - Degroote, Cathy; von Känel, Roland; Thomas, Livia; Zuccarella-Hackl, Claudia; Messerli-Bürgy, Nadine; Saner, Hugo; Wiest, Roland; Wirtz, Petra H. (Frontiers in Endocrinology, 2023)
Background. Coronary heart disease (CHD) and its major risk factor hypertension have both been associated with altered activity of the hypothalamus-pituitary-adrenal (HPA)-axis but the biological mechanisms underlying prospective associations with adverse disease outcomes are unclear. We investigated diurnal HPA-axis activity in CHD-patients, unmedicated hypertensive (HT) and healthy normotensive men (NT) and tested for prospective associations with biological CHD-risk factors. Methods. Eighty-three CHD-patients, 54 HT and 54 NT repeatedly measured salivary cortisol over two consecutive days. Prospective CHD-risk was assessed by changes between baseline and follow-up in the prothrombotic factors D-dimer and fibrinogen, the pro-inflammatory measures interleukin (IL)-6, tumor necrosis factor-alpha (TNF-α), and acute phase protein C-reactive protein (CRP), as well as blood lipids in terms of total cholesterol (tChol)/high-density-lipoprotein cholesterol (HDL)-ratio. We aggregated coagulation and inflammatory measures to respective indices. Results. The groups differed in repeated daytime cortisol (dayCort) secretion (p=.005,η2p=.03,f=0.18) and cortisol awakening response (CAR) (p=.006,η2p=.03,f=0.18), with similarly lower overall dayCort and CAR in CHD-patients and HT, as compared to NT. The groups differed further in cortisol at awakening (p=.015,η2p=.04,f=0.20) with highest levels in HT (p´s≤.050), and in diurnal slope between waking and evening cortisol (p=.033,η2p=.04,f=0.20) with steepest slopes in HT (p´s≤.039), although in part not independent of confounders. Lower aggregated dayCort and CAR in terms of area-under-the-curve (AUC) independently predicted increases in future overall CHD-risk (AUCdayCort: p=.018,η2p=.10,f=0.33;AUCCAR: p=.027,η2p=.09,f=0.31) 3.00±0.06(SEM) years later, with risk prediction most pronounced in fibrinogen (AUCdayCort: p=.017,ΔR2=0.12;AUCCAR: p=.082). Conclusion. We found evidence for hypocortisolism in CHD and HT with lower diurnal HPA-axis activity predicting increases in cardiovascular risk as evidenced by increases in circulating levels of biomarkers of atherothrombotic risk. Down-regulation of basal HPA-axis activity may contribute to the pathogenesis of atherosclerosis and thrombosis in CHD via effects on coagulation.